2020
DOI: 10.1161/circoutcomes.120.006938
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Critical Care Transfers for ST-Segment–Elevation Myocardial Infarction, Stroke, and Aortic Emergencies

Abstract: The COVID-19 pandemic has dramatically impacted healthcare delivery worldwide. In hotspot areas such as Wuhan, Lombardy, and New York City, the disease has forced hospitals to focus on COVID-19 patients. Anecdotal reports have suggested that the pandemic has led to a decrease in patients presenting to these hospitals with serious cardiovascular and neurologic diseases such as ST-elevation myocardial infarction (STEMI) and stroke. We sought to measure the impact of the COVID-19 pandemic on emergency transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 3 publications
3
22
0
Order By: Relevance
“…Notably, the authors observed a significant reduction in the number of ruptured and symptomatic aortic aneurysms. These findings are in line with those of most authors, who reported a substantial and precipitous drop in the monthly surgical case volume in emergency [22] . El-Hamamsy et al [23] declared a 76.5% reduction (12.8 ± 4.6 cases/month before COVID-19 to 3.0 ± 1.0 cases/month after COVID-19; P = .007) in hospitalizations for type A dissection in New York during March and April 2020.…”
Section: Resultssupporting
confidence: 92%
“…Notably, the authors observed a significant reduction in the number of ruptured and symptomatic aortic aneurysms. These findings are in line with those of most authors, who reported a substantial and precipitous drop in the monthly surgical case volume in emergency [22] . El-Hamamsy et al [23] declared a 76.5% reduction (12.8 ± 4.6 cases/month before COVID-19 to 3.0 ± 1.0 cases/month after COVID-19; P = .007) in hospitalizations for type A dissection in New York during March and April 2020.…”
Section: Resultssupporting
confidence: 92%
“…Of note, pacemaker implantations following aortic valve interventions were excluded in this analysis indicating a true reduction of emergency admission for severe bradycardia. Interestingly, even in the field of acute aortic syndromes requiring surgery there were marked decreases in patient numbers reported from both Europe to the US 32,33 . Regardless of this, treatment numbers in cardiac surgery were reduced by ~50% up to 75% both in areas with low and even pronounced in those with high COVID‐19 case numbers 34 .…”
Section: Discussionmentioning
confidence: 99%
“…2A). Diverse hospitals reported increasing levels of patients affected by stroke during SARS-CoV-2 infection [129,130]. Klok and colleagues observed disturbing increases in the incidence of thrombotic complications in critically ill intensive care unit patients as high as 31% and recommended pharmacological prophylaxis against thrombosis [24].…”
Section: P2x7 Receptors In Bbb Permeabilitymentioning
confidence: 99%